The Influence of the Availability of Environmentally Friendly Food on Consumers’ Green Purchasing Behavior - Hagag, Abdallah (Journal of Global Economy, Business and Finance, 2024)
For a long time, scientists, intellectuals, and environmentalists around the world have advocated for adopting an eco - friendly lifestyle. Unmindful human activities over the past few decades have caused irreversible damage to the Earth's ecosystem. Green marketing, or sustainable marketing, has emerged as a highly effective tool to address the problem of environmental degradation. The present era can be seen as a time of revelation and introspection regarding the impact of human activities on the environment. With the emergence of deadly diseases, it is imperative to recognize the importance of a healthy lifestyle. It is essential to motivate people to adopt products with green attributes by employing appropriate green marketing strategies. The present research paper attempts to analyses the impact of availability of eco - friendly food products on consumer buying behaviour.